RECONSTRUCTION OF THE ROLE OF WOMEN IN THE INTELLECTUAL HISTORY OF PATANI ISLAM - Khirpal Fikri (Journal Analytica Islamica, 2026)
The historiography of Islam in Patani has long been dominated by narratives of political conflict and intellectual history centered on male scholars and manuscript traditions. As a result, the contributions of women to the development of Islamic intellectual traditions in Patani have received limited scholarly attention. This study aims to reconstruct the role of women in the intellectual history of Islam in Patani while identifying historiographical biases that have contributed to their marginalization in previous studies. The research employs a historical method with a critical historiography approach combined with a qualitative systematic literature review. Data were collected from scholarly books and journal articles published between 1990 and 2025 that discuss Patani history, Pondok institutions, Islamic education, and gender relations. The analysis was conducted through historiographical criticism, close reading, and reading against the grain to uncover traces of women's involvement that have remained obscured within dominant historical narratives. The findings reveal that the limited representation of women in Patani's Islamic historiography is not due to the absence of their contributions, but rather to the dominance of conflict-oriented perspectives and text-centered approaches that regard manuscripts as the primary indicator of intellectual authority. This study demonstrates that Tok Guru Perempuan played a significant role in the transmission of religious knowledge, the management of female Pondok institutions, basic Islamic education, the preservation of Jawi literacy, and the maintenance of intellectual networks among ulama families. During periods of political crisis, women also functioned as key actors in sustaining Islamic education and preserving Malay-Muslim identity in Patani. Therefore, women should be recognized as an integral part of Patani’s Islamic intellectual history whose contributions have largely been overlooked in historical writing. This study highlights the importance of developing a more inclusive historiography to achieve a more comprehensive understanding of the development of Islam in Southeast Asia.